Organic and inorganic source fertilizer application reduces seedling diseases, insect pest occurrence and enhances growth performance of Citrus limon (L.) in Arba Minch, South Ethiopia - Yadda, Tuma Ayele; Hancho, Mulukem Elto; Mengesha, Getachew Gudero (Journal of Scientific Agriculture, 2025)
Lemon, Citrus limon (L.) Burm, is one of the vital fruit crops in terms of vitamins and minerals. Citrus anthracnose, leafminer (CLM), butterfly (CBF), and soil fertility problems are the main production constraints throughout the growing stages worldwide, including in Ethiopia. The study was designed to evaluate the sole as well as combined effects of powdered flowers of Hagenia abyssinica, farmyard manure (FYM), and blended nitrogen-phosphorus-sulfur (NPS) fertilizer on the citrus anthracnose, CLM, and CBF intensity as well as the growth performance of lemon seedlings. The experiment was conducted with eight treatments under various ratios of H. abyssinica, FYM, and NPS fertilizer in a simple and integrated manner at the main station of the research center for two consecutive years, 2021 and 2022. The treatments were arranged in a randomized complete block design with three replications. The results revealed a significant (P<0.05 to <0.0001) difference among the evaluated treatments for all study parameters. Accordingly, the lowest anthracnose incidence (8.75%), severity (5.54%), and area under the disease progress curve (131.66% days) were noted for powdered flowers of H. abyssinica (50 g, 100%). Similarly, this treatment showed the lowest CLM percent infestation (10.36%), larval density (0.49), CBF percent infestation (7.42%), and injury level (7.12%). A remarkable treatment difference for quantitative high-growth performance was observed in plant height (69.45 cm), number of primary branch lengths (24.28), number of primary (12.91), secondary (7.97), and tertiary (3.55) leaves, and total number of leaves per plant (310.50) from the application of H. abyssinica (50 g, 100%), while the highest leaf area (13.43 cm2) and stem girth (1.22 cm) were recorded from FYM (5 kg, 100%) applied ones. The unmanaged control plot had higher anthracnose, CLM, and CBF intensity as well as lower growth performance. Overall, among the evaluated treatments, powdered flowers of H. abyssinica (50 g, 100%) showed the best performance in terms of reducing anthracnose, CLM, and CBF intensity and enhancing the growth performance of the seedlings, so it could be suggested for lemon-growing farmers to manage their seedlings for anthracnose, CLM, and CBF. However, further research that comprises powdered flower of H. abyssinica on quality as well as quantity, along with other proper agronomic practices over locations and years, is required to develop a concrete recommendation for the wider community about the roles of the combination of organic and inorganic fertilization in minimizing citrus anthracnose, leafminer, and butterfly effects and for well-beingness seedling growth and physiological activities of lemon. Moreover, molecular characterization is essential to understand the specific nature of the C. gloeosporioides infecting lemon seedlings.